Digital Vulnerability and the Formulation of Harmonised Rules for Algorithmic Contracts: A Two-Sided Interplay - Rodriguez, Teresa de Las Heras Ballell (The New Shapes of Digital Vulnerability in European Private Law, 2024)
This book provides an analysis on whether and how the current European legal framework adequately deals with personal conditions in which digital...

The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal - Kane, Ibrahima (The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On, 2024)
"Chapter 16 The Impact of the United Nations Human Rights Treaties on the Domestic Level in Senegal" published on 09 Feb 2024 by Brill | Nijhoff.
Section: The Impact of the United Nations Human Rights Treaties on the Domestic Level: Twenty Years On
Keywords: Comparative Social Sciences; Human Rights; Human Rights and Humanitarian Law; Humanitarian Law; International Law; International Law: Regional Perspectives; Social Sciences

Part XV Chapter 2, Conciliation beyond the courts: aspirations and limits of mandated and voluntary court mediation programmes from a multi-jurisdictional perspective - Ali, Shahla (Comparative Procedural Law and Justice, 2024)
Keywords: Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Climate Change Litigation in Civil Law African Countries: An Assessment of Barriers and Potentialities in Cameroon - Mbarga, Daniel Armel Owona (Climate Litigation and Justice in Africa, 2024)
It seems like a long time ago that there were only a handful of climate lawsuits. Since the first climate lawsuits were filed in the United States in 1990,² a myriad of litigation has emerged at the national, regional and global levels. According to the Grantham Research Institute on Climate Change and the Environment, as of May 2021 the databases on climate litigation around the world contained 1,841 cases that were either in progress or had already been decided.³ This shows the exponential development of the phenomenon through which civil society organizations, public law legal entities and private individuals are
Keywords: Africa; Cameroun; Civil Law; Climate change; Litigation

Corporate Data Responsibility - Sarfaty, Galit A. (Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold, 2023)
This is an accepted manuscript of a book chapter in the edited volume: Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold
This file is under embargo and will become available on 2024-12-14

Chapter 1, Introduction to contract law and theory - DiMatteo, Larry A. (Principles of Contract Law and Theory, 2023)
This chapter provides background information on the evolution of the common law of contracts. It begins with a short history of the evolution of the common law in England including the roles played by the Roman Catholic Church, the development of a dual court system—one in law and the other in equity, the transition from absolute monarchy to a parliamentary form of government, the creation and restrictiveness of the English writ system, the common law’s reception in America, and the building of a general law of contract in the nineteenth century. It explains the historical differences between law and equity, along with the fusion of the two into a single court system. It also discusses the justifications given for contract law and its role in society. It describes the different perspectives of written or formal law, theory, and practice, and importantly, the difference between law in the books versus law in action. Finally, it explains the differences between rules, principles, and standards, and the boundaries of contract relative to other areas including tort and unjust enrichment.

Chapter 11, First principles in transportation law and policy - Levine, Jonathan; Shill, Gregory H. (A Research Agenda for US Land Use and Planning Law, 2023)
The main purpose of transportation is connecting people to destinations they value. This seemingly banal statement would, if taken seriously in policymaking, upend transportation and land use planning. Today, planning agencies rely on key performance indicators (KPIs) to measure outcomes. While ostensibly neutral and technical, these measurements in fact imply policy judgments and drive legal consequences. They operate both as a shield against litigation and as a sword to justify new projects. But the way KPIs are set up reflects confusion about basic purposes. They are used to plan and evaluate based not on the ability to reach anything but rather simply to accelerate the speed of traveling. We seek to anchor transportation policy discussion in first principles. The shift we propose is mode agnostic in that it is relevant to all means of transportation. Even so, shifting from a goal of speed to one of reachability would be a leap. We believe such a shift suggests important open questions regarding the barriers to reform and we engage a few of them.

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

La mise en concurrence des systèmes juridiques nationaux et l’idée de Constitution économique - Salah, M. Mahmoud Mohamed (The Idea of Economic Constitution in Europe, 2022)
Conséquence de la compétition que les États se livrent pour attirer le maximum d’investisseurs, la mise en concurrence des systèmes juridiques nationaux s’est traduite par une libéralisation continue du droit qui a eu un effet direct sur l’idée de Constitution économique. Celle-ci a non seulement vu son épaisseur normative se renforcer du fait de la neutralisation des dispositifs juridiques dirigistes mais elle s’est également universalisée en raison de la conversion de la quasi-totalité des pays au dogme de « l’attractivité ». Toutefois, ce mouvement généralisé vers le tout libéral commence à être remis en cause sous l’effet de facteurs divers qui se traduisent par une demande sociale et politique pour plus de régulation étatique. Il en résulte à la fois un regain de l’unilatéralisme qui affecte la force des principes qui sous-tendent l’idée de constitution économique et une prise en compte plus affirmée des valeurs et intérêts collectifs qui altère la substance de ces principes.
Section: The Idea of Economic Constitution in Europe
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

Do corporate governance codes matter in Africa? - Areneke, Geofry; Khlif, Wafa; Kimani, Danson; Soobaroyen, Teerooven (Research Handbook on Corporate Board Decision-Making, 2022)
Africa is often depicted in the literature as the ‘patron late to the party’ on account of her low uptake of corporate governance codes. Notwithstanding, countries that have an existing corporate governance code continue to exhibit weak corporate accountability and governance practices. This prompted a critical analysis based on a detailed review of published articles and existing codes in the African multiple-contexts. Our findings reveal that the efficacy of many codes remains very limited in terms of pragmatic outcomes whilst firms in countries that have adopted codes continue to face uneven performance and poor accountability. We conclude by urging for an understanding of the reasons underlying such results. We recommend an African led re-think (independence, ownership, board processes) of existing codes to make them more aligned with the governance needs of African firms and their complex sociocultural background. We call for further research to illuminate Africa’s actual governance experiences and necessities.
Keywords: Africa; African principles; Board of directors; Boardroom processes; Codes; Corporate governance; Developing countries; Neo-colonialism

The (Domestic) Enforcement of AU International Economic Law Instruments: Exploring the Desirability of Direct Effect - Simo, Regis Yann (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
This chapter deals with the principle of direct effect as applied in European Union law and explores its suitability in the enforcement of African Union (AU) legal instruments, notably those setting up the African Continental Free Trade Area (AfCFTA). What motivates the issue of direct effect is the noted reticence of African countries to litigate trade matters between themselves despite the existence of provisions of regional trade treaties creating courts of justice which give standing to Member States. Therefore, it surveys the avenues through which natural and legal persons can uphold their rights stemming from AfCFTA treaties thus contributing to treaty interpretation and increasing security and predictability. Currently, the AfCFTA Dispute Settlement Protocol, modelled after the WTO, does not allow such a possibility, contrary to rights acquired by natural and legal persons before some African Regional Economic Communities (RECs) courts. Nevertheless, this chapter finds that carving out access of natural and legal persons to AfCFTA proceedings may not always work as intended since there are other ways to bypass these obstacles. These loopholes could be the gateway through which direct effect will develop and become a principle of AU law broadly speaking. These gaps further complement this chapter’s suggestions to explore amending the AfCFTA legal instruments, even though its dispute settlement system is yet to be tested, in order to match the standing that natural and legal persons have acquired under the RECs, which, in fine, are building blocs towards achieving the AfCFTA and, eventually, the African Economic Community.
Keywords: AfCFTA; Africa; Direct effect; International Economic Law; International Law; International Trade Law; Regional courts; Regional integration

Chapter II: The Arbitrator and the Arbitration Procedure, An Arbitrator’s Imperative – How to Avoid Disappointing the Parties, Preventing Surprises and Enabling Efficient and Progressive Arbitral Proceedings - Welser, Irene; Mimnagh, Samuel (Austrian Yearbook on International Arbitration, 2021)

International Investment Law in African Courts - Mbengue, Makane Moïse; Schacherer, Stefanie (International Investment Law: An Analysis of Major Decisions, 2020)
This chapter identifies major categories of situations, events and institutions in which or through which questions of international investment law have been dealt with before African courts. The chapter is selective in nature and aims at showing tendencies instead of exhaustivity. A noteworthy tendency that becomes apparent through the chapter’s analysis is that the prevailing narrative of bypassing African courts and tribunals seems declining in importance as an increasing number of national investment law instruments foresee African judicial and arbitral institutions for the settlement of investment disputes.
Keywords: African national courts; Apartheid; EAC; ECOWAS; Investment arbitration; Land reform; National investment law; OHADA

Critical reflections on the development of integrated reporting: Are integrated reporting and IFRS competing frameworks? - Barker, R.; Teixeira, A. (The Routledge Handbook of Integrated Reporting, 2020)
Although integrated reporting emphasizes the contemporaneous relationship between financial and non-financial capitals, its primary purpose is to explain how an organization creates value over time. This is similar to the purpose of management commentary, which is part of a general-purpose financial report. We compare and contrast the information requirements of an integrated report with the type of information that supplements the primary financial information in general purpose financial reports, prepared in accordance with International Financial Reporting Standards (IFRS). We examine whether the information in those reports is intended to be forward-looking and predictive, whether non-financial capitals can (and should) be monetized in order to facilitate integration, and whether the reporting boundary should be drawn in different ways to serve different purposes. We find that the International Integrated Reporting Framework and IFRS do not serve different purposes or apply different approaches, but that – in essence – they are competing frameworks. While IFRS has highly developed standards for reporting financial capital, neither has a well-developed approach for reporting any other capital.

Corporate Shares as Shares - Katz, Larissa (Modern Studies in Property Law, 2019)
In this chapter, I ask whether shares in corporations ought to command more attention within theories of property. Contemporary liberal property theorists typically take land (and sometimes goods) as the basic case of property. Shares tend to be left out of these accounts or treated as imitations or mutations of the basic case. Economists, for their part, have transformed the idea of ownership: ‘owner’ refers to the ultimate beneficiary of the value of assets. Shares are treated as a central case of property by those who take this approach. Shareholders are taken to own the corporation insofar as they are the ultimate beneficiaries of its value. In this chapter, I concede shares do not fit within the traditional property framework. This does not mean, however, that the traditional idea of property is obsolete and that a new property framework is in order.
Accepted: 2023-06-22T17:00:40Z ISBN: 9781509921379 Publisher: Hart Publishing

Women in private international law - Keyes, Mary E. (Research Handbook on Feminist Engagement with International Law, 2019)
There has been almost no consideration of the position of women in private international law. There is very little published research applying a feminist analysis to, or even considering the position of women in, private international law. This field gives almost no attention to the particular interests, positions and experiences of women as subjects of the law, or the contribution of women as makers of the law. In the common law, private international law was largely developed in the 19th century, by male judges who were strongly influenced by commentary written exclusively by men. This chapter establishes that the apparently gender-neutral nature of private international law conceals profoundly ingrained assumptions about gender, in which the masculine is represented as a rational and sophisticated businessman, and the feminine is represented as a legally incapable wife. It then considers the gendered dimension of private international law in international family law, referring in particular to the regulation of international child abduction, international family property agreements, and international commercial surrogacy. Each of these examples demonstrates the differential impact of the law on women, indicating the need for greater awareness of and attention to gender. It concludes that while there have been some advances recently, particularly in terms of increased representation of women in making and commenting on private international law, there remains a great need for further research into the position of women as legal subjects and law-makers in this field.
Keywords: Private International Law; Woman

International Trade, Environment and Sustainable Development - Ruppel, Oliver C. (Environmental law and policy in Cameroon - Towards making Africa the tree of life | Droit et politique de l'environnement au Cameroun - Afin de faire de l'Afrique l'arbre de vie, 2018)
Issues related to international trade and the environment undoubtedly are of significance to developing countries like Cameroon because they argue that developed countries have depleted resources and indulged in environmentally harmful practices during the past century, in order to achieve unprecedented high standards of living.² The developing countries therefore demand a general but differentiated responsibility, seeking open trade and compensation for adopting environmentally restraining policies.³ Upon further reflection on the link between economic growth activities, environmental protection and social development, the triangular debate on these topics will be highlighted briefly, by introducing the various perspectives.⁴ Trade creates the wealth, which

Disqualification Decisions under the ICSID Convention and Arbitration Rules - Cleis, Maria Nicole (The Independence and Impartiality of ICSID Arbitrators, 2017)
This Chapter aims to distill a consistent approach to arbitrators’ independence and impartiality from past decisions on disqualification requests. In a first part, the interpretation of the manifest lack requirement provided for in Article 57 icsid Convention is scrutinized. The definition of this threshold (i.e. the burden of proof imposed on the challenging party) is crucial, because it determines the effectiveness of the right to an independent and impartial decision-maker. The second part of the Chapter inquires how specific categories of alleged conflict are dealt with. It seeks to derive consistency and predictability from the outcome or reasoning of disqualification

Institutional and Contextual Factors Effects on Entrepreneurship in Cameroon: The Case of the Transport Sector - Okah-Efogo, Françoise; Okah-Atenga, Crescence Marie-France (Entrepreneurship in Africa, 2017)
In Africa, whatever the considered age group, there are more entrepreneurs in the early stages of entrepreneurship than anywhere else in the world (Global Entrepreneurship Monitor (GEM) Report 2014). According to the gem survey (2014), 55.57 per cent of the population between 18–64 years expresses entrepreneurial intentions in Cameroon. Similarly, 37.4 per cent of the same age population is in the early course of their business activity. Between 2014 and 2015, total entrepreneurial activity has decreased in Cameroon (from 37.4 per cent to 25.4 per cent of all adults). Nonetheless, 61.1 per cent of the respondents think that entrepreneurship

Regional Integration in Africa through the Harmonisation of Laws - Simo, Regis Yann (Regional Integration and Policy Challenges in Sub-Saharan Africa, 2014)
Domestic laws on the African continent have been considered inadequate to attract the investment needed for development and economic growth. A crucial catalyst in attracting investment on the continent is law reform. The formulation of legislation has twofold effects: firstly, it is perceived to mitigate the risks associated with doing business in Africa; secondly, it legally obligates African governments to comply with standards of protection accorded to international investors through the regulation of the business environment. The formulation of legislation is a key determinant of the quality of investment attracted to the continent. This Chapter assesses how the Organization for the Harmonization of African Business Law (OHADA) has contributed to regional integration and economic growth on the continent.
Keywords: Africa; Institutions; Law Reform; OHADA; Regional integration

Legal Innovation for Development: The OHADA Experience - Frilet, Marc (Legal Innovation and Empowerment for Development, 2013)
The World Bank legal review gathers this input from around the world and compiles it into a useful resource for all development practitioners and scholars. The subtitle of this volume, legal innovation and empowerment for development, highlights how the law can respond to the chal-lenges posed to development objectives in a world slowly emerging from an economic crisis. The focus on innovation is a call for new, imaginative strategies and ways of thinking about what the law can do in the development realm. The focus on empowerment is a deliberate attempt to place the law into the hands of the poor; to give them another tool with which to resist poverty. This volume shows some of the ways that the law can make an innovative and empowering difference in development scenarios. Development problems are complex and varied, and the theme of innovation and empowerment naturally has a broad scope. Consequently, this volume reaches far and wide. It considers the nature, promise, and limitations of legal innovation and legal empowerment. It looks at concrete examples in places such as Africa, the Asia-Pacific region, and Latin America. It considers developments in issues with universal application, such as the rights of the disabled and the effectiveness of asset recovery measures. The theme of legal innovation and empowerment for development complements substantive and institutional sensibilities in current development policy. Substantively, development policy discourse seems to have moved away from tacking hard toward statist policy or neoliberal policy. Although this brief introduction cannot do justice to the richness and complexity of these contributions, it does consider each focal point in turn.

Chapter 42, Dissenting Opinions by Party-Appointed Arbitrators in Investment Arbitration - van den Berg, Albert Jan (Looking to the future: essays in international law in honor of W. Michael Reisman, 2010)
Dissenting opinions appear to have become an accepted practice in international arbitration. Th e current debate concentrates on their procedure, form, and content. Alan Redfern noted that “[a]t present, a generally relaxed attitude towards dissenting opinions seems to be taken not only by the arbitral institutions, but also by the arbitrators themselves … .” In this contribution, I would like to explore the cautionary note with which Redfern concluded his seminal article, namely, that the “[t]ime has perhaps come to inquire whether the present leniency towards dissenting opinions … has gone too far.” I propose to do so with respect to investment arbitrations because ade available publicly, particularly party-appointed arbitrators’ dissenting opinions.
Keywords: Arbitrage; Arbitration; Arbitrator; Dissenting opinion; Investment arbitration; Opinion dissidente

Rethinking consumer protection policy - Trebilcock, Michael (International Perspectives on Consumers' Access to Justice, 2003)
This is the version of record of an article authored by Michael Trebilcock and published by the Cambridge University Press.

International Trade & International Labour Standards - Trebilcock, Michael (International Economic Governance and Non-Economic Concerns, 2002)
This is an accepted manuscript of an article authored by Michael Trebilcock, and later published in International Economic Governance and Non-Economic Concerns.
Accepted: 2023-08-02T19:59:53Z
Keywords: International Labour Standards; International Trade; Labour law; NAFTA; Unfair competition; WTO

International trade policy and domestic food safety regulation: The case for substantial deference by the WTO Dispute Settlement Body under the SPS Agreement - Trebilcock, Michael; Soloway, Julie (The Political Economy of International Trade Law: Essays in Honor of Robert E. Hudec, 2002)
There has been a dramatic shift in the focus of trade policy concerns in recent years from the barriers that lie at the border to the barriers which exist “within the border.” The General Agreement on Tariffs and Trade/World Trade Organization (GATT/WTO) and other regional trading arrangements have been largely successful in reducing both the levels of tariffs worldwide and the scale of other border measures such as quotas. This has revealed a new and more subtle category of measures which restrict trade – the numerous regulations which governments enact to protect the health and safety of their citizens and the environment in which they live. Such regulations vary tremendously across borders: one nation's bunch of grapes is another nation's repository of carcinogenic pesticide residue. These efforts to protect citizens from the hazards of everyday life have become a virtual minefield for trade policy makers, in part because such differences can often be manipulated or exploited to protect domestic industry from international competition, and in part because even when there is no protectionist intent on the part of lawmakers, through a lack of coordination, mere differences in regulatory or standard-setting regimes can function to impede trade through increasing multiple compliance costs. It has thus become increasingly difficult to delineate the boundaries between a nation's sovereign right to regulate and its obligation to the international trading community not to restrict trade.
Accepted: 2023-08-02T20:19:47Z
Keywords: GATT; International Trade; Trade Policy; WTO

Intellectual Property Rights and Competition: A Framework for the Analysis of Economic and Legal Issues - Gallini, Nancy; Trebilcock, Michael (Competition Policy and Intellectual Property Rights in the Knowledge-Based Economy, 1998)
This is the version of record of a chapter authored by Nancy Gallini and Michael Trebilcock, and published by the University of Calgary Press.
Accepted: 2023-08-03T16:16:10Z
Keywords: Competition Policy; Economic Literature Review; Intellectual property